KONSEP BIMBINGAN KONSELING ISLAM DALAM MENINGKATKAN MORAL REMAJA - Jannah, Miftahul (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2021)
Islamic counseling guidance is a form of knowledge as well as a form of assistance to provide direction in solving problems properly. Especially on teenage morale. Adolescence is often used and misunderstood. Both in terms of association, social, and the environment. In fact, the important point that must be cultivated in the soul of youth today is good morality ethics. In fact, adolescents today have experienced significant setbacks. Very few teenagers have and understand how moral ethics are in social, social and environmental terms. Some opinions say that the souls of teenagers are souls who have more curiosity than usual, want to try things that should not be in accordance with their youthful condition. In this case, a very important role is needed to accompany the growing adolescence. Namely parents and the school environment are very influential roles to limit, oversee how the process of healing children who are approaching adolescence. By guiding and strengthening faith in God almighty. In addition, Islamic counseling guidance is also a good means of providing direction, sharing about problems being experienced by adolescents. Previous counseling guidance adopted more concepts and practices developed by western scientists. However, with the rampant Islamization of knowledge, sharing activities to explore Islamic concepts and values are increasingly being carried out. So counseling guidance is transformed into Islamic counseling guidance. It contains concepts that contain religious values. There are various kinds of delinquency committed by adolescents, so there is a need for proper guidance to deal with adolescent problems, by seeing the rampant juvenile delinquency at this time, which is lacking in good ethical and moral values. The purpose of Islamic counseling guidance in improving adolescent morale is an optimal development, namely development in accordance with the potential and value systems of a good and right life. Optimal development is not merely the achievement of a high level of intellectual ability, which is characterized by mastery, knowledge, and skills, but an academic condition, where individuals are able to know and understand themselves, dare to accept self-reality objectively, direct themselves according to their abilities and opportunities. , and can make choices and make decisions on their own responsibility. Therefore, this paper aims to determine the concept of guidance in improving morale for adolescents with Islamic values. The method used in this research is library research by exploring sources of moral improvement for today's adolescents through studies in books, articles and other scientific works. The role of Islamic counseling guidance greatly contributes to improving the morale of adolescents in interacting with the surrounding environment which is based on Islamic teachings.